Resource Optimization for Time Slot-Split Noma in Full-Duplex Cooperative Communications. (September 2020) - Sun, Fugang; Li, Chuanqing; Liu, Yi; Wang, Xuan; Liu, Yi
Abstract: A time-slot-split non-orthognal multiple access (TSS-NOMA) scheme for full-duplex (FD) relaying communication systems is proposed to improve frequency resource utilization. Aiming at the problem of low bandwidth efficiency when users pairing, TSS-NOMA divides the whole time slot into several parts to improve the matching process, where users can occupy all bandwidths in different time slots. TSS-NOMA decodes the information symbols of relay and re-encodes the messages through the new power allocation factors of successfully matched users. The mixed symbols are sent to increase the proportion of central users' own signals received by themselves, thus improving the performance of the system. To maximize the minimum achievable rate of the system, TSS-NOMA optimizes the power allocation at the base station and the relay. Numerical results show that TSS-NOMA can achieve higher spectral and energy efficiency than some existing schemes.